2018
DOI: 10.1016/j.watres.2018.02.066
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in pharmaceutical concentrations in an urban river system

Abstract: Many studies have quantified pharmaceuticals in the environment, few however, have incorporated detailed temporal and spatial variability due to associated costs in terms of time and materials. Here, we target 33 physico-chemically diverse pharmaceuticals in a spatiotemporal exposure study into the occurrence of pharmaceuticals in the wastewater system and the Rivers Ouse and Foss (two diverse river systems) in the city of York, UK. Removal rates in two of the WWTPs sampled (a conventional activated sludge (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(98 citation statements)
references
References 51 publications
8
86
4
Order By: Relevance
“…As a complement, Burns et al . and Paíga et al . observed that in influents of wastewater treatment plants, the contaminant in question obtained the most significant concentrations, resulting in higher effluent loads after inefficient treatment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a complement, Burns et al . and Paíga et al . observed that in influents of wastewater treatment plants, the contaminant in question obtained the most significant concentrations, resulting in higher effluent loads after inefficient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment of water and wastewater is often unable to remove pharmaceuticals completely, including acetaminophen, which is discharged continuously in aqueous environments . Therefore, it is necessary to investigate complementary methods to effectively remove such pharmaceutical pollutants from water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, spatial and temporal variations in pharmaceutical usage and environmental conditions might impact the accuracy of exposure predictions. (Burns et al 2018). Currently, there are no apparent models or initiatives to include this temporal variability in exposure predictions, which is a limitation of both prioritization and risk assessment initiatives.…”
Section: Navigating the Frameworkmentioning
confidence: 99%